Evaluasi dan Arahan Peningkatan Pelayanan Air Bersih di Kota Makassar - Arthur Toding; Mimi Arifin; Yashinta Kumala Dewi Sutopo (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2021)
Clean water services are still a problem faced by the Makassar City government, South Sulawesi. The high demand for clean water services is currently not being handled properly. The aim of this research is to determine the factors that affect clean water services and the problems. This research was conducted from April 2019 to January 2020 (10 months). This research used primary and secondary data. The analysis used in this research is descriptive analysis with qualitative and quantitative approaches and spatial analysis through mapping using the ArcMap application. The results showed that the factors affecting clean water services in Makassar City are clean water sources, production capacity, location, number of people served, climate, water loss (leakage), water treatment management, and financing. Problems experienced by the community in clean water services in Makassar City are leaks, not running water, checking bills, problematic meters, dirty and smelly water, broken pipes, problematic payments and others (new installation and moving meters). To fulfill the need for clean water in Makassar City, can be added with additional water sources which are processed and distributed to the community, by using water from rivers around Makassar City and utilizing rain water harvesting or seawater desalination. In addition, it is necessary to improve the clean water distribution system and water treatment management from the source to the distribution of water to the community to reduce the level of water loss.